Pattern Analysis on Wireless Network Coverage in DISPERKIM, South Sumatra - Irwansyah, .; Imam, Al Akbar; Misinem, .; Helda, Yudiastuti (INTI International University, 2024)
The study's focus on pattern analysis provides a data-driven approach to optimizing WI-FI networks, ensuring better connectivity and reliability for users within the South Sumatra Provincial Housing and Residential Area Office. These results have broader implications for the strategic deployment of WI-FI in similar environments. WI-FI technology, utilizing the IEEE 802.11a/b/g wireless standard operating at 2.4 GHz, is ubiquitous in environments such as government offices, private companies, entertainment venues, and educational institutions. The growing reliance on WI-FI for internet access, driven by the proliferation of WI-FI-enabled devices, underscores the importance of optimizing its deployment for efficient connectivity. This study examines the WIFI signal patterns and range in the WLAN network at the South Sumatra Provincial Housing and Residential Area Office, where suboptimal placement of WI-FI access points has hindered network performance. By conducting a field survey and pattern analysis of signal distribution and coverage, the research identifies critical gaps and inefficiencies in the current wireless setup. Employing the action research methodology, the study progresses through four stages: diagnosis, action planning, action tackling, and evaluation. The analysis of signal strength patterns and coverage data guides targeted improvements to optimize WI-FI placement. Findings are expected to reveal how spatial factors and interference impact signal distribution, offering actionable insights for enhancing wireless network performance.